Evidence of suppression of onchocerciasis transmission in the Venezuelan Amazonian focus. Issue 1 (December 2016) - Botto, Carlos; Basañez, María-Gloria; Escalona, Marisela; Villamizar, Néstor; Noya-Alarcón, Oscar; Cortez, José; Vivas-Martínez, Sarai; Coronel, Pablo; Frontado, Hortencia; Flores, Jorge; Graterol, Beatriz; Camacho, Oneida; et al.
Abstract Background The World Health Organization (WHO) has set goals for onchocerciasis elimination in Latin America by 2015. Most of the six previously endemic countries are attaining this goal by implementing twice a year (and in some foci, quarterly) mass ivermectin (Mectizan®) distribution. Elimination of transmission has been verified in Colombia, Ecuador and Mexico. Challenges remain in the Amazonian focus straddling Venezuela and Brazil, where the disease affects the hard-to-reach Yanomami indigenous population. We provide evidence of suppression ofOnchocerca volvulus transmission bySimulium guianense s.l. in 16 previously hyperendemic Yanomami communities in southern Venezuela after 15 years of 6-monthly and 5 years of 3-monthly mass ivermectin treatment. Methods Baseline and monitoring and evaluation parasitological, ophthalmological, entomological and serological surveys were conducted in selected sentinel and extra-sentinel communities of the focus throughout the implementation of the programme. Results From 2010 to 2012–2015, clinico-parasitological surveys indicate a substantial decrease in skin microfilarial prevalence and intensity of infection; accompanied by no evidence (or very low prevalence and intensity) of ocular microfilariae in the examined population. Of a total of 51, 341 S. guianense flies tested by PCR none had L3 infection (heads only). Prevalence of infective flies and seasonal transmission potentials in 2012–2013 were, respectively, under 1 % and 20 L3/person/transmission season. Serology in children aged 1–10 years demonstrated that although 26 out of 396 (7 %) individuals still had Ov-16 antibodies, only 4/218 (2 %) seropositives were aged 1–5 years. Conclusions We report evidence of recent transmission and morbidity suppression in some communities of the focus representing 75 % of the Yanomami population and 70 % of all known communities. We conclude that onchocerciasis transmission could be feasibly interrupted in the Venezuelan Amazonian focus.